Corrigendum: A large light-mass component of cosmic rays at 1017-1017.5 electronvolts from radio observations - Buitink, S.; Corstanje, A.; Falcke, H.; Hörandel, J.; Huege, T.; Nelles, A.; Rachen, J.; Rossetto, L.; Schellart, P.; Scholten, O.; Ter Veen, S.; Thoudam, S.; et al. (Nature Publishing Group, 2016)
In this Letter, we omitted to cite preliminary results from the low-energy extension of the Pierre Auger Observatory, as presented at the International Cosmic Ray Conference 2015 (ref. 1). Figure 1 of this Corrigendum shows measurements of the average value of Xmax for the Low Frequency Array (LOFAR), and earlier experiments using different techniques, now including the data from the Pierre Auger Observatory1, specifically the contribution of A. Porcelli. Our values are in agreement with those of ref. 1 within systematic uncertainties. - Nature 531, 70–73 (2016); doi:10.1038/nature16976